Unlimited semiosis: contributions to thinking about subject indexing - Reis, Daniela Majorie Akama dos (2021)
Subject Indexing, as part of Information treatment, is the process responsible to define terms that portray documents main subjects. Later, these terms are converted into subject entries, and at the end of the process the subject entries are inserted into information systems. Subject Indexing is an important process for Information Science. However, there are no formalized manuals and guidelines that indicate how the indexer should be guided in the structure of the document. Semiotics is considered the science of signs, and brings a fresh perspective to researches in information science. The contributions of Semiotics to the field of information processing become apparent when the concept of Unlimited Semiosis is used to explain the steps of Subject Indexing. Therefore, we present some aspects of Semiotics in order to explain how they relate to the Subject indexing process and how its nature can be revealed through it.